(untitled) (Świat Idei i Polityki, 2022)
The essence of political myths, their structure and key functions have been analyzed in the article. The peculiarities of the political myths’ creation in the Ukrainian society have been also characterized. It has been determined that political myths are an effective tool of influencing the political culture and consciousness of the citizens and that they are being used by the present-day Ukrainian politicians in order to gain and keep power. The attention to the predominantly destructive role of political myths in the development of modern Ukrainian society has also been drawn in the article. The authors claim that with the development of the information society a political myth is becoming more adaptive and gains the ability to create an illusion of reality and its manipulative influence is becoming more masterly and less noticeable. This influence often leads to the simulation of the democratic principles, depression and passive attitude of the citizens. It is possible to minimize the social consciousness manipulation through raising the level of the political culture and consciousness of the citizens, forming an open communication system between authorities and citizens, developing independent mass media, etc.